Effect of supplementary lighting on nutrient recovery of Ocimum basilicum and fishes in a polyculture aquaponic system - Junaid, Azeezat Adenike; Kamarudin, Mohd Salleh; Wahab, Puteri Edaroyati; Junaid, Quazim Olawale; Okomoda, Victor Tosin; Isyaka, Mohammed Sani; Adejola, Yusuf Adewale; Umar, Danladi Mohammed; Amin, Sarker Mohd Nurul (BioMed Central, 2023)
The effects of prolonged photoperiod (additional night lighting) were investigated on the production of Ocimum basilicum (lemon basil) and fish/crayfish raised in a nutrient film technique aquaponic system. Hybrid lemon fin barb and red claw crayfish juveniles were co-cultured with O. basilicum and subjected to 12 h of ambient natural daylight and additional 0, 4, 8, and 12 h of night lighting for 14 weeks (two batches of 7 weeks each). The water quality parameters and the performance characteristics of the fish/crayfish/plant were evaluated, and the nutrient uptake (nitrogen, phosphorus, and potassium) in the system by the three organisms was also measured. The fish growth performance showed no significant differences (p > 0.05) in all the growth parameters measured across the treatments. The body proximate and nitrogen, phosphate, and potassium (NPK) composition of the fish and crayfish were not significantly (p > 0.05) different across the treatments. Similarly, there was no significant difference (p > 0.05) in the NPK uptake by the fish and crayfish across the treatments. The plant growth performance showed that there were no significant (p > 0.05) differences in the plant growth parameters measured, except for % plant height gained in the 12 h-light treatment (403.2 ± 26.0%) which was significantly (p < 0.05) higher than other treatments and cycles. Hence, this study demonstrated that varying supplementary night lighting has no significant effect on the growth performance of O. basilicum, hybrid lemon fin barb, and red claw crayfish. This study, therefore, suggests that supplementary night lighting should not be considered for O. basilicum production as it does not significantly improve the performance characteristics of the plant nor the fish co-cultured with it in a polyculture aquaponic system.